A rare location of Crohn’s disease: the nasal mucosa - Pellicano, R.; Sostegni, R.; Sguazzini et al., C. (Acta Biomedica Atenei Parmensis, 2011)
Crohn’s disease (CD) is a chronic inflammatory disease that affects both the small and large intestine in approximately 40% of cases, solely the ileum or the colon in 30% and 25%, respectively. The remaining locations of the gastrointestinal (GI) tract are involved in percentages ranging between 0.5 and 5%. The appearance of the disease outside the GI tract is an exceptional event. In the present case, the authors report the history of a male patient suffering from CD involvement of almost the entire digestive system plus the nasal mucosa. This latter event emerged after repeated episodes of epistaxis, the demonstrations of histologic nasal features similar to those of intestinal CD, and the remission after treatment with beclomethasone. Since in literature less than a decade of cases of nasal location of CD was described, it is of prime importance to highlight that in CD patients, the occurrence of repeated episodes of epistaxis should prompt a consideration in the differential diagnosis of nasal location of the disease.